Proline content in the leaves of poplar and willow under water deficit - Y. A. Khoma; O. G. Nesterenko; N. K. Kutsokon; L. V. Khudolieieva; V. V. Shevchenko; N. M. Rashydov (Regulatory Mechanisms in Biosystems, 2021)
Water deficiency is one of the most important abiotic factors limiting the growth and productivity of plants. Under conditions of water deficiency, plants can synthesize osmoprotectors, in particular proline. The aim of our work was to estimate the accumulation of free proline in the leaves of two poplar clones ‘Slava Ukrainy’, ‘Guliver’ and willow clone ‘Pechalna’ in water-deficient conditions. Plants were grown outdoors, providing protection from the rain with a plastic wrap, with a differentiated watering: normal watering –100% (control) and water deficit – 75%, 50 % and 25% moisture by volume from the control. The content of free proline was determined by a modified Bates method by measuring the optical density of the ninhydrin-proline solution on a spectrophotometer at a wavelength of 520 nm. Experimental observations have shown that the total content of proline differs among poplar and willow clones. The poplar ‘Guliver’ had a lower content of proline compared to the poplar ‘Slava Ukrainy’ and the willow ‘Pechalna’. The level of free proline also differed between the samples of poplar ‘Guliver’ in the first and second years of growth under water deficiency. However, on the 30th day of treatment we did not find any differences in the content of proline between the stressed and control plants. Thus, the clone factor has the only obvious effects on proline content while the factor of water regime showed no effects on the level of proline. We hypothesize that water deficiency is more likely to alter proline levels as a shorter time response to stress than the terms we applied.